Analysis and Implementation of University Teacher Salary Prediction Based on Decision Tree Regression Model - Lei, Shanwen (International Journal of Computer Science and Information Technology, 2024)
This study is based on the decision tree regression model, utilizing the Python programming language and third-party libraries such as Scikit-learn, to mine and analyze data of university teachers over the past five years. A decision tree regression model is constructed, enabling the prediction and analysis of university teacher salaries. This achievement provides university administrators with a more scientific, objective, and efficient decision-making reference, aiding in the construction of a more scientific and systematic budget management system for universities.